UNDERSTANDING MARITAL DISPUTES MANAGEMENT IN RELIGIOUS OFFICE AND SYARIAH COURT IN MALAYSIA - Zakiyah, Zakiyah (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2014)
This article reviews a monograph entitled Managing Marital Dispute in Malaysia, Islamic Mediators and Conflict Resolution in the Syariah Court written by Syarifah Zaleha Syed Hassan  and Sven Cederrot. This book contributed in the discourse of anthropology of Islamic law. This book discussed about three institutions that dealt with Islamic family law; kadi, women counselor and judge. This monograph was published in 1997 when Islamic family law became one of the heated topics in many part of the world. This book was a result of extensive research conducted at the religious office and syariah court in Kedah and Johor Malaysia. This study shows that mediator used different ways in dealing with the family disputes including formal, semi formal and informal. The first method was used to deal with adjudication, the second was utilized to manage arbitration, and the last was used in consultation, conciliation and mediation. In addition, ?kadi?, women counselor  and the judge not only use legal formal approach but also local norm when giving advice and managing cases.